Evaluation of multi-modal in-vehicle computer interface on driving performance - Pow, Lay Ling. (2008)
Multi-modal in-vehicle computer system is continuously increasing in functionality and complexity due to the advance technology and car manufacturers are trying to offer these functions to their customers. The effect of using multi-modal in-vehicle computer system while driving is a concern to the human factor experts. This paper presents an experiment to research whether the visual presentation of a multi-modal in-vehicle computer acts as redundancy or complementary modality for auditory presentation will aids in relieving the resource demand. Two multimodal interfaces constructed were "MP3 player" and "Accommodation Booking".